Post-War Jewish Fiction - Brauner, D. author. aut Link
XI, 222 p.
Keywords: In this groundbreaking study, David Brauner explores the representation of Jewishness in a number of works by postwar British and American Jewish writers, identifying a transatlantic sensibility characterised by an insistent compulsion to explain themselves and their Jewishness in ambivalent terms. Through detailed readings of novels by famous American authors such as Saul Bellow, Philip Roth, Bernard Malamud and Arthur Miller, alongside those by lesser-known British writers such as Frederic Raphael, Jonathan Wilson, Howard Jacobson and Clive Sinclair, certain common preoccupations emerge: Gentiles who mistake themselves for Jews; Jewish hostility towards Nature; writing (and not writing) about the Holocaust, and the relationship between fact and fiction.